DALAM PEMBELAJARAN MATEMATIKA MELALUI PERMAINAN BOWLING PADA ANAK TUNAGRAHITA RINGAN - ROFIAH, AINUR (Jurnal Pendidikan Khusus, 2018)
ABSTRACT. The problem in this research was the low ability of mild mentally retardation children of class II in SLB Aisyiyah Tulangan – Sidoarjo to mathematics subject matter of 1 – 10 addition material. This research had purpose to know the children’s ability to the material of 1 – 10 addition in learning mathematics through bowling game. This research was a class treatment research using descriptive qualitative approach. The subject in this research was mild mentally retardation children of class II in SLB Aisyiyah Tulangan – Sidoarjo which consisted of 4 boys and 2 girls. The instruments used in this research were the observation of children’s activities sheet and evaluation in the end of lesson. Through bowling game, learning mathematics of 1 – 10 addition could enhance the learning result of the mild mentally retardation children of class II in SLB Aisyiyah Tulangan – Sidoarjo. This was proved by the enhancement of the children’s learning result to each meeting so that it reached 7,3 above the criteria standard of minimum completeness determined by the school i.e. 7,0. The children’s learning acitvity using bowling game to 1 – 10 addition ran well and effectively. The children’s response toward bowling game in mathematics subject matter with the material of 1 – 10 addition was very positive and fun.     Keywords: Learning mathematics, bowling game